ChemInform Abstract: Reaction of 6‐Aminouracils with Aldehydes in Water as Both Solvent and Reactant under FeCl3·6H2O Catalysis: Towards 5‐Alkyl/Arylidenebarbituric Acids. Issue 7 (29th January 2015) - Kalita, Subarna Jyoti; Mecadon, Hormi; Chandra Deka, Dibakar
Abstract For the first time the title products are prepared regioselectively from 6‐aminouracils, which presents an alternative to the known procedures from barbituric acids.